Echo Color Doppler Ultrasound: A Valuable Diagnostic Tool in the Assessment of Arteriovenous Fistula in Hemodialysis Patients. Issue 5 (September 2016) - Mudoni, Anna; Caccetta, Francesco; Caroppo, Maurizio; Musio, Fernando; Accogli, Antonella; Zacheo, Maria Dolores; Burzo, Maria Domenica; Gallieni, Maurizio; Nuzzo, Vitale
A functioning vascular access is a critical requirement to improve the quality of life in hemodialysis patients, so monitoring and surveillance of vascular access play key roles in identifying all dysfunctions and reducing the huge economic cost as well as adequacy of dialysis. In our five-year experience, a study protocol has been used and improved with the help of ultrasonography. Doppler ultrasound is an excellent and sensitive modality for hemodialysis access evaluation, one of techniques employed for arteriovenous fistulae (AVF) study, not only as a pre-operative tool, but also in post-operative monitoring of AVF maturation. In addition, the current guidelines recommend AVF surveillance by access blood flow measurement and the correction of hemodynamic stenosis in order to prolong access survival. Doppler ultrasound is readily available, directly used by nephrologists, non-invasive, safe, inexpensive, reproducible, although it requires more clinical skill and time to perform and proper equipment. Ultrasonography imaging can substantially reduce the number of subsequent invasive angiographic procedures. In our opinion, Doppler ultrasound should have a crucial place in the interdisciplinary cooperation in AVF monitoring and it should be included as part of an integrated vascular access management program.